Credible Commitment in Covert Affairs. Issue 3 (27th April 2018) - Spaniel, William; Poznansky, Michael
Abstract: A recurring challenge in politics is to convince actors to take cooperative actions against their self‐interest. This is especially challenging for executives conducting covert activities, as infractions are unobservable and institutional reforms often require the executive's consent. We develop a model based in the auditing literature to investigate when executives agree to reforms that credibly constrain their behaviors. If the revelation cost falls in a high range, the risk of whistleblowing convinces executives to restrain themselves. Executives cannot credibly commit to this when the costs are low, resulting in inefficient investigations from watchdog groups that tax executive resources. We show that executives are sometimes better off in the first case than the second, which results in executives endogenously reforming institutions to achieve this outcome. We illustrate the mechanism with a case study of Gerald Ford's executive reforms to the intelligence community in the 1970s.